Atherogenic dyslipidemia and cardiovascular risk in children with nonalcoholic fatty liver disease. (June 2011) - Alkhouri, Naim; Carter-Kent, Christine; Elias, Michael; Feldstein, Ariel E
Nonalcoholic fatty liver disease is now regarded as the most common form of chronic liver disease in adults and children. The close association between nonalcoholic fatty liver disease (NAFLD) and the metabolic syndrome has been extensively described. Moreover, a growing body of evidence suggest that NAFLD by itself confers a substantial cardiovascular risk independent of the other components of the metabolic syndrome. Given the significant potential for morbidity and mortality in these patients, and the large proportion of both pediatric and adult population affected, it is important that we clearly define the overall risk, identify early predictors for cardiovascular disease progression, and establish management strategies. In this article, we will focus on current data linking NAFLD and the severity of liver damage present in children with cardiovascular risk.